Identification and analysis of the FAD gene family in walnuts (Juglans regia L.) based on transcriptome data - Kai Liu; Shugang Zhao; Shuang Wang; Hongxia Wang; Zhihua Zhang (BMC Genomics, 2020)
Abstract Background Walnut kernels contain a large amount of unsaturated fatty acids, such as linoleic acid and linolenic acid, which are essential fatty acids for humans and have important effects on growth and health. The main function of fatty acid desaturase (FAD), which is widely distributed in organisms, is to remove hydrogen from carbon chains in the biosynthesis of unsaturated fatty acids to generate C=C bonds. Results By performing a series of bioinformatics analysis, 24 members of the JrFAD gene family were identified from the genome database of walnut, and then compared with the homologous genes from Arabidopsis. Phylogenetic analysis showed that JrFADs were classified into four subfamilies: the SAD desaturase subfamily, Δ7/Δ9 desaturase subfamily, Δ12/ω-3 desaturase subfamily and “front-end” desaturase subfamily. Meanwhile, the expression of fatty acid synthesis genes in walnut kernels at different developmental stages was analysed by transcriptome sequencing, with expression of JrFAD3-1, which encodes an enzyme involved in linolenic acid synthesis, being particularly prominent. The relative expression level of JrFAD3-1 changed dramatically with the kernel development stages and exhibited a Bell-Shaped Curve. A significant positive correlation was observed between the expression of JrFAD3-1 during 70–100 DAF (Days after flowering) and the content of alpha-linolenic acid during 100–130 DAF, with a correlation coefficient of 0.991. Additionally, JrFAD3-1 was proved closely related to homologous genes in Betula pendula and Corylus heterophylla, indicating that the conserved structure of FADs is consistent with classical plant taxonomy. Conclusion Twenty-four members JrFADs in walnut were identified and classified into four subfamilies. JrFAD3-1 may play significant roles in the biosynthesis of polyunsaturated fatty acids in walnut.